The classifications of subaxial cervical spine traumatic injuries. Part 4. AOSpine Subaxial Classification System - Nekhlopochyn, Oleksii S.; Slynko, Ievgenii I.; Verbov, Vadim V. (Ukrainian Neurosurgical Journal, 2021)
Cervical spine injuries are a fairly common consequence of mechanical impact on the human body. The subaxial level of the cervical spine accounts for approximately half to 2/3 of these injuries. Despite the numerous classification systems that exist for describing these injuries, the recommendations for treatment strategy are very limited, and currently none of them is universal and generally accepted. Consequently, treatment decisions are based on the individual experience of the specialist, but not on evidence or algorithms. While the classification system based on the mechanism of trauma originally proposed by B.L. Allen et al. and subsequently modified by J.H. Harris Jr et al., was comprehensive, but lacked evidence, which to some extent limited its clinical applicability. Similarly, the Subaxial Injury Classification System proposed by the Spine Trauma Group, had no distinct and clinically significant patterns of morphological damage. This fact hindered the standardization and unification of tactical approaches. As an attempt to solve this problem, in 2016 Alexander Vaccaro, together with AO Spine, proposed the AO Spine subaxial cervical spine injury classification system, using the principle of already existing AOSpine classification of thoracolumbar injuries. The aim of the project was to develop an effective system that provides clear, clinically relevant morphological descriptions of trauma patterns, which should contribute to the determination of treatment strategy. The proposed classification of cervical spine injuries at the subaxial level follows the same hierarchical approach as previous AO classifications, namely, it characterizes injuries based on 4 parameters: (1) injury morphology, (2) facet damage, (3) neurological status, and (4) specific modifiers. The morphology of injuries is divided into 3 subgroups of injuries: A (compression), B (flexion-distraction), and C (dislocations and displacements). Damage types A and B are divided into 5 (A0-A4) and 3 (B1-B3) subtypes, respectively. When describing damage of the facet joints, 4 subtypes are distinguished: F1 (fracture without displacement), F2 (unstable fracture), F3 (floating lateral mass) and F4 (dislocation). The system also integrates the assessment of neurological status, which is divided into 6 subtype). In addition, the classification includes 4 specific modifiers designed to better detail a number of pathological conditions. The performance evaluation of AOSpine SCICS showed a moderate to significant range of consistency and reproducibility. Currently, a quantitative scale for assessing the severity of classification classes has been proposed, which also, to a certain extent, contributes to decision-making regarding treatment strategy.